2016
DOI: 10.1016/j.jana.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reiki With Music Compared to Music Only Among People Living With HIV

Abstract: Persons living with HIV (PLWH) often seek complementary treatments to improve their overall health and well-being. Reiki, an ancient healing practice, has been found to be effective in reducing symptoms of stress, anxiety, pain, and depression. The purpose of this pilot study was to evaluate the effectiveness of Reiki as a complementary treatment for PLWH. Using a two-group mixed-methods experimental design, 37 participants were randomized to either a 6-week Reiki with Music Group or a Music Only Group. Self-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
22

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 1 publication
1
18
0
22
Order By: Relevance
“…Music therapy is a recognized discipline linked to improved hemodynamics in patients with chronic illness (Raghavan & Eknoyan, 2014). In the past few years, nurse researchers have studied the effects of music with rigorous randomized controlled trials in several care settings such as surgical (Ugraş et al, 2018), critical care (Hetland et al, 2017), neonatology (Taheri, Jahromi, Abbasi, & Hojat, 2017), AIDS care (Bremner, Blake, Wagner, & Pearcey, 2016), and cardiology (Burrai, Hasan, Fancourt, Luppi, & Di Somma, 2016). In numerous studies involving patients receiving hemodialysis, music ameliorated a variety of complications including pain, cramps, and itching (Koca Kutlu & Eren, 2014).…”
mentioning
confidence: 99%
“…Music therapy is a recognized discipline linked to improved hemodynamics in patients with chronic illness (Raghavan & Eknoyan, 2014). In the past few years, nurse researchers have studied the effects of music with rigorous randomized controlled trials in several care settings such as surgical (Ugraş et al, 2018), critical care (Hetland et al, 2017), neonatology (Taheri, Jahromi, Abbasi, & Hojat, 2017), AIDS care (Bremner, Blake, Wagner, & Pearcey, 2016), and cardiology (Burrai, Hasan, Fancourt, Luppi, & Di Somma, 2016). In numerous studies involving patients receiving hemodialysis, music ameliorated a variety of complications including pain, cramps, and itching (Koca Kutlu & Eren, 2014).…”
mentioning
confidence: 99%
“…Several scientific studies show health benefits of Reiki therapy, such as: pain relief (6)(7)(8)(9) , the reduction of stress and anxiety (9)(10) , better coping with illness and therapeutic processes (11) , decreased blood pressure (9) , improvement of depressive symptoms (12) and sleep problems (13) . However, most of these studies have methodological designs that make little room for the expression of the centrality of the subject in the care process.…”
Section: Introductionmentioning
confidence: 99%
“…8 Complementary therapies, such as Reiki, have seldom been studied in newborns. Studies on Reiki in the adult population have shown a decrease in pain 9 11 and stress 10 , 11 without affecting vital signs. 9 11 However, little or no research has documented the feasibility and safety or the immediate results of such an intervention, on neonatal parameters.…”
Section: Introductionmentioning
confidence: 99%